Production of dayside ionosphere of Mars - Singh R.N.; Prasad R. (My University, 2025)
Choosing an appropriate neutral-density model of martian atmosphere, the photoionization processes have been studied. Using relevant charge transfer and recombination reactions, the equilibrium electron-ion production rates have been computed for all species. The resultant electron-density profiles are compared with the ones measured experimentally by Viking 1 and 2. The theoretical electron-density profile compares well with the measured profiles at low altitudes, but shows rather large values at higher altitudes. The observed oscillation in the electrondensity profile at high altitudes is attributed to the variable nature of impact ionization produced by suprathermal charged particles of solar wind origin. © 1983 Indian Academy of Sciences.